Strategic plan for Davao Oriental Coco Husk Social Enterprise Incorporated - Pogosa, Bernardita N. (School of Management, University of the Philippines Mindanao, 2012)
Davao Oriental Coco Husk Social Enterprise Incorporated (DOCHSEI) is a social enterprise not only by its name but also by its purpose. DOCHSEI aims to significantly contribute to the economic growth of the rural areas through the processing of new added-value products, generating employment and reducing the migration of workers in the locality to the big cities. DOCHSHEI fulfills this description of the social enterprise paradigm which is the very foundation of its organization, to exist not only for profit but for the benefit of the larger community which it serves. The company?s capital investment has been sourced out from foreign donors and Unlad Kabayan, a non-government organization helping the marginalized coconut farmers in the province. Since there are no shareholders in a non-profit organization, the profits from the related social enterprise are completely re-invested in the work of the organization. Eventually, capital investment flowed in from a private sector and various government agencies. The founders are committed to continue making a difference in the lives of the marginalized sector by converting the farm waste material (coco husk) to usable and exportable products. The international market remains volatile yet promising. The price of coco fiber is fluctuating over time. When the price is low, the company opts to store the coco fiber produced which may result to a huge volume of its inventory. Hence, this makes the production inefficient. Despite the challenges in poor market accessibility, DOCSHEI has managed to survive these economic constraints. What it needs is a full vision, guidance and direction. This strategic plan carves the pathway towards growth by maximizing potentials of the social enterprise. DOCHSHEI is set to take the path of product development. The potential of coco coir industry is big and the by-products are not yet explored to its maximum utilization. The global demand is seen to rise, while the domestic market is still left untapped. These are the factors that inspire DOCHSEI to move towards fulfilling its ultimate dream. The succeeding pages will open the plans and possibilities for coco coir industry, and the control system to achieve the vision, mission, and objectives of DOCSHEI.